2020
DOI: 10.1152/japplphysiol.00281.2020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and isometric handgrip exercise increases wave reflection in healthy young adults

Abstract: Early return and increased magnitude of wave reflection augments pulsatile load, wastes left ventricular effort, and is associated with cardiovascular events. Acute handgrip (HG) exercise increases surrogate measures of wave reflection such as augmentation index. However, augmentation index does not allow distinguishing between timing vs. magnitude of wave reflection, and is affected by factors other than wave reflection per se. Wave separation analysis decomposes central pressure into relative contributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 51 publications
2
24
1
Order By: Relevance
“…We recently found that central blood pressure also increased during handgrip exercise, but wave separation analysis parameters responded differently. For example, in the present study Pf increased while Pb and RM decreased, but during handgrip exercise Pf did not change while Pb and RM increased (Stock et al, 2020). The RWTT decreased in both studies, suggesting that the exercise modality does not influence reflected wave timing, whereas pressure wave amplitudes are affected differentially.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…We recently found that central blood pressure also increased during handgrip exercise, but wave separation analysis parameters responded differently. For example, in the present study Pf increased while Pb and RM decreased, but during handgrip exercise Pf did not change while Pb and RM increased (Stock et al, 2020). The RWTT decreased in both studies, suggesting that the exercise modality does not influence reflected wave timing, whereas pressure wave amplitudes are affected differentially.…”
Section: Discussioncontrasting
confidence: 52%
“…The vasoactive response during LBD appears to limit the impact of wave reflection on the left ventricle, whereas we have shown that handgrip exercise transiently increases the work imposed on the left ventricle as a result of wave reflection (Stock et al, 2020).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations